Pendugaan Bobot Badan Melalui Ukuran Shank pada Ayam Kampung yang Dipelihara Secara Tradisional di Manokwari - N Zurahmah; M A Mu'in; J A Palulungan (Politeknik Negeri Lampung, 2023)
This study aims to find an estimator of body weight by means of shank length and shank circumference in adult Kampung chickens reared traditionally. A total of 173 adult Kampung chickens (79 males and 94 females), aged 1 year belonging to several breeders in Prafi District, Manokwari Regency, were used as material for this study. Best Subsets Regression analysis was used to find the best body weight estimation model for this research chicken. The results showed that shank length (PSJ) was the best estimator of body weight (BBJ) for adult male Kampung chickens through the formula: BBJ = 0.363 PSJ – 1.67, because it had the best accuracy rate (highest R2 and lowest C-p and s) compared to the formula others available. For adult female Kampung chickens, shank length (PSB) and shank circumference (LSB) are the best estimators of body weight (BBB) for adult female Kampung chickens using the formula: BBB = 0.205 PSB + 0.127 LSB - 0.864, because it has the best level of accuracy (R2 highest and C-p and lowest s) compared to other available formulas. These formulas are very well applied to Kampung chicken farms that are kept traditionally in an area in order to choose good male candidates and prospective brooders for that area.